Partisipasi Perempuan Pedagang Keliling dalam Membantu Ekonomi Keluarga di Kabupaten Sorong - Hikmah Hasanah; Syahrul Syahrul (At-Thariqah: Jurnal Ekonomi, 2021)
The purpose of this study is to describe how women's participation in helping the family economy, their factors in working and how their portraits work as traders. This research is a field research located in the Malasom Village, Sorong Regency. The method of this research is a qualitative. Data collection was carried out by observation, interviews and documentation. The result of the research is that according to the Islamic viewpoint, womens participation in helping the family economy by means of working is permissible, in accordance with the requirements in Islam, namely getting permission from the husband, not neglecting household affairs and taking care of themselves. The traders in Malasom Village have met these requirements. The form of womens participation in helping the family economy is by working as traders, such as selling vegetables, porridge, sempol, herbal medicine, cakes, toast and tela-tela. The factors behind their work to help the family economy are economic factors, husband's income, age, work experience and education.